Warped axions - Flacke, T; Gripaios, B; March-Russell, J; Maybury, D (2007)
We study a number of realizations of axions existing in a multi-'throat' generalization of the warped throat geometry of a Randall-Sundrum slice of AdS5. As argued by previous authors, the problem of generating a suitable, phenomenologically allowed Peccei-Quinn scale is simply and elegantly solved by the warping. In compactifications with two or more throats it is possible to simultaneously solve the Standard Model hierarchy problem by the Randall-Sundrum mechanism while implementing interesting warped axion models. The constructions discussed are related to holographic duals of previously studied models of composite axions arising from strongly coupled four-dimensional dynamics. © SISSA 2007.